Early Resumption of Peritoneal Dialysis Post Laparoscopic Appendectomy: A Case Report and Literature Review - Mohadese Golsorkhi MD; Lakshmi Ganesan MD; Sergio Infante MD; Amir Abdipour MD (SAGE Publishing, 2023)
Abdominal pain and fever in patients on peritoneal dialysis (PD) raise suspicion of PD-associated peritonitis. However, other causes of peritonitis such as appendicitis should be considered. The laparoscopic approach is the standard of care in many of these situations. This technique allows PD catheter preservation and early resumption of PD. Here, we report a case where PD was resumed successfully 48 hours after laparoscopic appendectomy. A 45-year-old man with end-stage renal disease on chronic PD presented with acute abdominal pain. On examination, the patient was febrile and had lower abdomen tenderness without a rebound. The exit site of the PD catheter was clean. An initial diagnosis of PD-associated peritonitis was made, and an intraperitoneal antibiotic was given. Abdominal computed tomography revealed appendicitis. It was confirmed that the patient had severe nonperforated appendicitis following a laparoscopic appendectomy. The PD catheter was preserved, although the patient reported good residual kidney function; his electrolyte abnormalities with rising creatinine and potassium indicated the need to resume dialysis. Low-volume PD in a strict supine position was resumed 48 hours after surgery. The patient tolerated low-fill PD without any complications. He was discharged home on post-op day 4, and further follow-up revealed no complications. Resuming PD early in patients who go under laparoscopic surgery with low-volume PD is a reasonable option in select cases. Close follow-up from the dialysis team to detect and manage complications is necessary.